2019
DOI: 10.1007/s10439-019-02261-w
|View full text |Cite
|
Sign up to set email alerts
|

Wall Stress and Geometry Measures in Electively Repaired Abdominal Aortic Aneurysms

Abstract: Abdominal aortic aneurysm (AAA) is a vascular disease characterized by the enlargement of the infrarenal segment of the aorta. A ruptured AAA can cause internal bleeding and carries a high mortality rate, which is why the clinical management of the disease is focused on preventing aneurysm rupture. AAA rupture risk is estimated by the change in maximum diameter over time (i.e., growth rate) or if the diameter reaches a prescribed threshold. The latter is typically 5.5 cm in most clinical centers, at which time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This is a significant reduction in computational time and power than using the smallest rotational increment of 0.5° (processing time of 218 min). Several reports that conducted FEA of AAA used MWS as a biomechanics metric since it provides guidance on whether an aneurysm, in a general sense, is at an elevated stress-state [ 12 , 14 , 15 , 16 , 17 , 19 , 25 ]. The 3D geometric reconstruction needed for computational analysis of AAAs can vary considerably.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a significant reduction in computational time and power than using the smallest rotational increment of 0.5° (processing time of 218 min). Several reports that conducted FEA of AAA used MWS as a biomechanics metric since it provides guidance on whether an aneurysm, in a general sense, is at an elevated stress-state [ 12 , 14 , 15 , 16 , 17 , 19 , 25 ]. The 3D geometric reconstruction needed for computational analysis of AAAs can vary considerably.…”
Section: Discussionmentioning
confidence: 99%
“…DICOM data was performed using a semi-automated approach with a U-NET convolutional neural network and custom MATLAB code (Mathworks, Natwick, MA, USA) [ 18 , 19 ] ( Figure 1 ). The U-NET was trained using Amazon Web Service’s (Amazon, Seattle, WA, USA) Elastic Compute Cloud and local workstations using multiple graphics processing units [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been shown that in addition to geometric indices such as D max , a variety of biomechanical parameters and material properties affect AAA morphology and behavior [3,[7][8][9]. Wall stress distribution and mainly the peak wall stress -which is directly related to the failure site on the AAA surface -computed using finite element analysis (FEA) have been helpful to comprehensively consider the effects of all mentioned parameters [10][11][12]. Additionally, it has been illustrated that patient-specific historical data, such as the presence of clinical pre-existing conditions or risk factors, such as smoking, hypertension, or chronic kidney disease (CKD) may increase AAA severity and risk of rupture [6,13].…”
Section: Introductionmentioning
confidence: 99%